The epidemiology of burn injury among children during COVID-19 19 pandemic and WFH policy in Malang, East Java, Indonesia - Herman Yosef Limpat Wihastyoko; Arviansyah Arviansyah; Erdo Puncak Sidarta (Intelektual Pustaka Media Utama, 2021)
Work from home (WFH) mandate is one of the major changes known during this pandemic, aimed as a preventive way to mitigate the spread of the COVID-19 virus. This study aimed to observe the characteristics of pediatric burn injury during COVID-19 pandemic and WFH mandate's impact on pediatric burn injury admission at some Hospital burn centers in Malang. Every patient’s age, gender, clinical characteristics, parent's background, and other variables such as the possession of siblings, response time using our burn registry form, and comparative analysis of the incident in WFH housewife mother were assessed. The majority were in the group age of under five years old group age (70%) with a mean of 5.5 years. The most frequent part of the burn injured is extremity 36.7%, and hot liquid dominates as the cause of the injury 73.3% with the total body surface area of burn injury group >10% is the most common 56.7%. The burn injury incident happened more frequently in mothers with children less than two in both groups. This study showed that the increase in increasement of the pediatric burn injury during COVID-19 pandemic between housewife mother and WFH mother has no significant difference also showed that parent especially mother unable to supervise the children during WFH. Strategies to mitigate pediatric burn injuries during WFH should be thoughtfully implemented.